Analysis of Alternative Strategies for Domestic Wastewater Systems Management and Development in Regency/City Governments (Case Study: South Tangerang City, Banten Province) - Nur Dewisri Fatihawati; Marisa Handajani (Journal of Social Research, 2022)
The impact of high urban population growth and increasing development activities in various sectors causes various problems in urban areas, one of which is wastewater pollution. Through the "Wastewater System Management and Development Program", where the planning activity program must be able to improve the management and development of domestic wastewater systems. Based on the results of the analysis in the application of planning activity programs in the study area, it can be influenced by several aspects, namely law &regulatory, technological/technical, institutional, community participation, environment and financing, with the highest participation rate in internal indicators of 52.45%, while external indicators of 47.55%. Meanwhile, the variables that have been identified based on the participation of the city government and community stakeholders in the management and development of the SPALD case study of South Tangerang City obtained for the identification analysis of the IFE matrix are 3.11 and EFE 2.79 so that the position of the main Planning Activity Program of South Tangerang City is in quadrant IV (growth and development strategy), while for SWOT quadrant analysis the axis value (X) is 1.02 and the axis (Y) is 0.99 so that the position of the model application is in quadrant I (aggressive support strategy). While the results of the alternative strategy analysis (QSPM) are the most priority, interesting and appropriate for the management and development of case studies of the Domestic Wastewater Management System (SPALD) of South Tangerang City, in this case referring to the results of participation through questionnaires and interviews with resource persons (stakeholders of the South Tangerang city government), obtaining the results of the analysis, namely the alternative Maintain Program strategy, namely developing and running simultaneously (Strategy Combination) between alternative strategies, with the order of Alternatives (1) Integrative Programs, amounting to 7.36, Alternative (3) Product Development, amounting to 7.19 and Alternatives (2) Market Penetration, amounting to 7.08.